La forêt et son imaginaire social : quels enjeux pour l’avenir ? - Yves Luginbühl (Projets de Paysage, 2020)
The forest has always been a fertile source of inspiration which has nourished the imagination of humankind and its relationship to nature. In different societies, depending on whether the forest is perceived as a bucolic, picturesque, sublime or romantic element, its role in the social representations of the landscape takes on more or less importance. The article seeks to focus on the significance of the forest in the history of social relationships to nature in several European countries, such as France and Germany for example, and which differ greatly from country to country. After describing the main features of this symbolic history of the forest in several European countries, the article examines more closely the relationships between the landscape, the forest, and the economy with as the main criterion the sense of well-being or unease experienced by people living close to forests.